Gout tophi on the soles resembling viral warts. Issue 6 (24th April 2018) - Bossart, Simon; Sidler, Daniel; Blum, Roland; Hunger, Robert E.
Key Clinical Message: This case highlights the need to consider tophaceous gout in patients with post‐transplant renal insufficiency, chronic immunosuppression, and hypertension, who develop atypical papules or nodules on the soles, which can cause problems in differentiation from other skin diseases. Abstract : This case highlights the need to consider tophaceous gout in patients with post‐transplant renal insufficiency, chronic immunosuppression, and hypertension, who develop atypical papules or nodules on the soles, which can cause problems in differentiation from other skin diseases.